Penyebaran Studi Hadis Di Qairawan: Studi Hadis Kawasan - Mayada, Wafiq (UIN Sumatera Utara Medan, 2025)
This study aims to understand the history of the development of Islam and the spread of hadith in Qairawan as well as the contribution of scholars to the spread of hadith in the region. The research method used is library research with data collection through books, theses, journals, and websites. The result of this study is that Qairawan has an important role in the history of the spread and development of hadith studies in North Africa. The city of Qairawan was built by Uqbah b. Nafi` during the Umayyad Dynasty, which became the center of advanced Islamic civilization and the fourth holy city after Makkah, Madinah, and Jerusalem. The spread of hadith in this region was supported by many scholars including Abu al-Arab al-Tamimi who was known as an important figure in the science of jarh wa at-ta`dil and contributed greatly to the teaching, narration and writing of books of hadith.